2015
DOI: 10.1093/rheumatology/kev295
|View full text |Cite
|
Sign up to set email alerts
|

Coping styles and disability in patients with hand osteoarthritis

Abstract: In patients with hand OA, joint-specific factors and coping styles decreasing activity and pacing were both associated with disability. Our results suggest that interventions should aim at joint-specific complaints as well as changing coping styles to improve functional outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…The longitudinal data on the hand outlined here did not confirm the role of pain as a mediator in the OA and physical function decline association that was uncovered during one of our cross‐sectional studies (11,35–38), but showed that pain was a confounder. In accordance with our previous results, the current study found associations between the participants’ physical function and psychological factors (39–41). Anxiety, which is an emotional reaction associated to a nonspecific stimulus, could lead to preventative behaviors, such as avoidance of potentially painful stimuli or activities (39).…”
Section: Discussionsupporting
confidence: 93%
“…The longitudinal data on the hand outlined here did not confirm the role of pain as a mediator in the OA and physical function decline association that was uncovered during one of our cross‐sectional studies (11,35–38), but showed that pain was a confounder. In accordance with our previous results, the current study found associations between the participants’ physical function and psychological factors (39–41). Anxiety, which is an emotional reaction associated to a nonspecific stimulus, could lead to preventative behaviors, such as avoidance of potentially painful stimuli or activities (39).…”
Section: Discussionsupporting
confidence: 93%
“…Although there is mixed evidence around the association between disease duration and progression of osteoarthritis (26), we found that those patients with newly diagnosed osteoarthritis (≤1 year) or those with long‐standing disease (≥10 years) were not at significantly increased risk of self‐harm. This finding could be due to patients with a recent diagnosis not yet having a prolonged negative experience of osteoarthritis, which could be a contributing factor to self‐harm, or those with very long‐standing osteoarthritis having developed coping mechanisms (27).…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by the contribution of psychosocial factors to self-reported disability. Examples of such factors are depression, illness perceptions, coping styles and anxiety [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%